Computational calibration of an abrupt expansion as a flow meter - Flores, Janett; Goicochea, Javier; Lucchese, Alessandro; Damia, Juan (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This paper establishes the conditions under which discharge and loss coefficients can be predicted, and the conditions which permit the use abrupt expansion as a measurement of flow. The prediction is done by a computer simulation based on PatankarÂ´s finite volume method, which resolves the continuity and quantity of movement equations for turbulent flow. The comparison of the results obtained with those available from other works, show that it is feasible to use abrupt expansion as a flow-meter and supports the effectiveness of the program utilized.